Особливості алюзивної репрезентації антропонімів в англомовному публіцистичному дискурсі - Ісмаїлова, Є. А.; Ismailova, E. A. (Волинський національний університет імені Лесі Українки, 2012)
У статті представлено класифікацію антропонімів за ознакою актуальності окремих характеристик первинного референта. Проаналізовано особливості The article deals with the concept of allusive anthroponym. The classification of anthroponyms on the basis of certain characteristics of primary referent is represented. Peculiarities of allusive anthroponym functioning in English journalistic discourse are analyzed.
Peculiarities of Allusive Representation of Anthroponyms in English Journalistic Discourse
Keywords: алюзія; allusion; алюзивний антропонім; allusive anthroponom; публіцистичний дискурс; journalistic discourse